Shariah governance framework of Islamic banks in Bangladesh: practices, problems and recommendations - Alam, Md. Kausar; Ab Rahman, Suhaimi; Mustafa, Hasri; Mohammed Shah, Sabarina; Hossain, Md Shamim (Asian Economic and Social Society, 2019)
Shariah Governance Framework (SGF) is a structural process by which Islamic banks monitor, control and conduct their activities. This study describes the overall scenery of SGF of Islamic banks in Bangladesh. The paper also reviews the current practices, problems, legal and regulatory issues by using a deductive procedure and provides some propositions for the enhancement of SGF. The main objective of this paper is to understand the SGF, its current practices, problems and challenges which will be helpful to develop a SGF for Islamic banks in future. The study reveals that the Shariah governance system in Bangladesh is mainly voluntary rather than regulatory and there is an absence of full-fledged SGF. It seems that the Board of Directors (BOD) uses the Shariah Supervisory Board (SSB) in accomplishing their objectives and responsible for overall Shariah activities rather than the SSB. In order to improve the SGF, Bangladesh government should enact a law for the operations of Islamic banks. Besides, Bangladesh Bank (BB) should come out with a comprehensive Centralized SGF by outlining the roles, powers, and functions of all stakeholders to ensure the accountability of their works and improve the quality of the Shariah compliance. Moreover, the central bank can set up a Central Shariah Supervisory Board (CSSB) in its head office or can recognize existing Central Shariah Board for Islamic Banks of Bangladesh (CSBIB) along with power so that they can supervise and monitor overall activities of Islamic banks and solve the disputes among the stakeholders regarding the Shariah issues of Islamic banks.